Sharp Rejection and Wide Stopband Microstrip Lowpass Filters using Complementary Split Ring Resonators - I. F. da Costa; A. L. P. S. Campos; A. Gomes Neto (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract Chebyshev microstrip lowpass filters with improved performance, achieved by means of circular complementary split ring resonators (CSRR), are presented. CSRR particles exhibit frequency rejection bandwidths in the vicinity of their resonant frequencies that can be used to meliorate both selectivity and stopband in microstrip lowpass filters. Two configurations have been used: a stepped-impedance model and a configuration using open-circuited stubs. Microstrip filters having 5, 7 and 9 poles were designed and fabricated. Selectivity values up to 86 dB/GHz and suppression levels reaching 60 dB in the stopband were obtained. The filters have cutoff frequency around 2 GHz and rejection band up to 10 GHz. The insertion of the designed CSRR resonators in the ground plane of the filters removes all the transmission spurious observed in the analyzed frequency band. No considerable variation in the passband group delay is observed in the CSRR-based lowpass filters. A comparison is made among the filters designed in this and other referenced works, considering their number of poles and size. The measured results are in good agreement with the simulated ones. The presented filters can be candidates for applications using the VHF, UHF and L bands, being also very effective in the rejection of the S and C bands. Applications that demand the rejection of the first half of the X band can also use the filters detailed in this paper.